Translation of the management control system in a privatised solid waste management network - Che Pak, Nur Azliani Haniza; Ismail, Suhaiza; Mohd Alwi, Norhayati (Emerald Publishing, 2024)
Purpose The purpose of this paper is to help better understand the translation process of the management control system (MCS) of privatised solid waste management (SWM) towards creating a stable network.